2022
DOI: 10.3389/fcomm.2021.777569
|View full text |Cite
|
Sign up to set email alerts
|

The Multilingual Pragmatics of New Englishes: An Analysis of Question Tags in Nigerian English

Abstract: This paper presents a variational pragmatic analysis of multilingual question tags in Nigerian English, combining a corpus-pragmatic analysis of the Nigerian component of the International Corpus of English with a survey study on the preferences and attitudes of Nigerian students toward different question tag forms. The corpus study highlights multilingual pragmatic variation in terms of form and function of variant as well as English and non-English (i.e., derived from indigenous Nigerian languages) invariant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Research in pragmatics has also been demonstrated to correlate with the clusters identified in our scientometric analysis. Among these studies are those investigating variations in pragmatic language learning in non-English contexts [ 145 ], aspects of politeness [ 146 ], using virtual reality for developing pragmatic language [ 147 ], pragmatics and reasoning [ 148 ], ritual interaction [ 132 ], hearing impairment and pragmatic language skills [ 149 ], autism and neural association of pragmatic language skills [ 150 ], linguistic prediction at the pragmatic language level [ 151 ], mind reading in pragmatics [ 152 , 153 ] and executive functions and pragmatic language skills [ 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in pragmatics has also been demonstrated to correlate with the clusters identified in our scientometric analysis. Among these studies are those investigating variations in pragmatic language learning in non-English contexts [ 145 ], aspects of politeness [ 146 ], using virtual reality for developing pragmatic language [ 147 ], pragmatics and reasoning [ 148 ], ritual interaction [ 132 ], hearing impairment and pragmatic language skills [ 149 ], autism and neural association of pragmatic language skills [ 150 ], linguistic prediction at the pragmatic language level [ 151 ], mind reading in pragmatics [ 152 , 153 ] and executive functions and pragmatic language skills [ 154 ].…”
Section: Discussionmentioning
confidence: 99%